2020
DOI: 10.3389/fmicb.2020.01554
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Novel Lytic Bacteriophages Infecting Epidemic Carbapenem-Resistant Klebsiella pneumoniae Strains

Abstract: Carbapenem-resistant Klebsiella pneumoniae (CRKP) poses a significant clinical problem given the lack of therapeutic options available. Alternative antibacterial agents, such as bacteriophages, can be used as a valuable tool to treat the infections caused by these highly resistant bacteria. In this study, we isolated 54 phages from medical and domestic sewage wastewater between July and September 2019 and determined their host ranges against 54 clinical CRKP isolates, collected from a te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 48 publications
6
27
0
Order By: Relevance
“…Consequently, the isolated phages have shown a broad host range against MDR K. pneumoniae isolates with 77% activity against MDR isolates. Similar results were also obtained in a recent study on MDR K. pneumoniae bacteriophages with a 96% host range against carbapenem MDR K. pneumoniae (30). However, bacteriophages isolated from Italy and Australia showed narrow host ranges.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Consequently, the isolated phages have shown a broad host range against MDR K. pneumoniae isolates with 77% activity against MDR isolates. Similar results were also obtained in a recent study on MDR K. pneumoniae bacteriophages with a 96% host range against carbapenem MDR K. pneumoniae (30). However, bacteriophages isolated from Italy and Australia showed narrow host ranges.…”
Section: Discussionsupporting
confidence: 89%
“…Briefly, the hospital wastewater was collected in locally purchased 500 mL plastic bottles. All plastic bottles were then tightly closed and wrapped in sterile bags (strip plastic bags) to avoid contamination (30). All bottles were placed on the benchtop to allow the large debris to settle down for 1 to 3 hours.…”
Section: Isolation Of Bacteriophagementioning
confidence: 99%
“…Several studies have detected major ESBL genes ( blaTEM , blaSHV , blaCTX-M and blaOXA ) in CRE strains [ 11 ]. Given the fact that carbapenem antibiotics are considered as the last resort for treating infections caused by ESBL-producing strains, presence of carbapenemase and ESBL genes in CRE strains coupled with lack new therapeutic option is cause for concern [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…MLST analysis showed that the K. pneumoniae strain KP32558 was assigned to ST656, a rare ST type and firstly reported in China in 2012 (36). The frequently detected carbapenemase in these bacteria was KPC-2 (37) and NDM-1 (38). Our study represents the first report of the emergence of NDM-5 and MCR in ST656 K. pneumoniae clinical isolate.…”
Section: Discussionmentioning
confidence: 56%